The Impact of Coaching Leadership on Employees' Positive Outcomes - Ribeiro, Neuza (2020)
Leaders resort to a coaching leadership style—which relies heavily on listening, helping, supporting, developing, removing obstacles, and empowering others— to promote valuable work experiences and positive attitudinal and behavioral responses from employees. These employees’ outcomes are an important part of organizational success. In this chapter, the authors examine the connection between coaching leadership style and employees’ affective commitment, creativity, and customer orientation. A quantitative study was carried out based on the perceptions of 80 front office workers from different Portuguese organizations on their leaders and their own attitudes and behaviors. The results, consistent with existing literature, indicated that, when leaders adopt a coaching leadership style, their followers are more affectively committed, exhibit more creative behavior, and perform in a more customer-oriented way.